EXIT from TRansrectal prostate biopsies (TREXIT): sepsis rates of transrectal biopsy with rectal swab culture guided antimicrobials versus freehand transperineal biopsy - Newman, Thomas Hedley; Stroman, Luke; Hadjipavlou, Marios; Haque, Arman; Rusere, Jonah; Chan, Kimberley; Ioannides, Demetris; Di Benedetto, Antonina; Pinczes, Tibor; Popert, Rick; Hammadeh, Mohamed Y. (Prostate cancer and prostatic diseases, 2022)
Background Transrectal prostate biopsy (TRUSBx) holds a risk of prostate biopsy related sepsis. We discuss our step-wise strategies aiming to reduce this risk, including targeted antimicrobials and switching to a freehand transperineal approach (FHTPBx). Subjects and methods This longitudinal cohort study included three groups. Group A underwent TRUSBx with empirical augmented antimicrobial prophylaxis; Group B underwent TRUSBx with targeted antimicrobial prophylaxis, based on rectal-swab cultures/sensitivity; Group C underwent FHTPBx with empirical antimicrobial prophylaxis. Post biopsy sepsis, defined according to the surviving sepsis campaign and confirmed with blood or urinary cultures, were determined and rates between groups were analysed using fisher’s exact test. Results Of all 1501 patients, 23 developed post biopsy sepsis; Group A (12/609, 2.0%), B (9/403, 2.2%), C (2/489, 0.4%). Targeted antimicrobials did not reduce the risk of post biopsy sepsis following TRUSBx (A vs B, 2.0% vs 2.2%; p = 0.82). Patients with antimicrobial-resistant rectal flora had an increased post biopsy sepsis rate following TRUSBx despite targeted antimicrobials (9.1% vs 1.1%, p = 0.003). Switching to FHTPBx reduced the risk of developing post biopsy sepsis (A vs C, 2% vs 0.4%, p = 0.03; B vs C, 2.2% vs 0.4%, p = 0.03). Conclusions Targeted antimicrobials based on rectal swab culture failed to reduce the overall risk of post biopsy sepsis, while FHTPBx nearly eliminated this risk. We recommend the use of transperineal prostate biopsies for all patients as the most effective method to reduce the risk of sepsis.